I (Do Not) Like Reading!: A Narrative Inquiry into Indonesian Highschoolers’ General Reading Motivation - Astra Belinda (Center of Language and Cultural Studies, 2020)
The study of motivation has been going around in the educational field for years long, but the issue is there are not many studies that specify in reading motivation, specifically for EFL and/or ESL students. Looking upon this concern, this narrative inquiry study tried to recognize the reasons behind the reading motivation amongst the students, particularly from Blue Star Senior High School, through the Self-determination Theory (SDT) principle from Deci & Ryan (1991) and some other possible social aspects, such as family and peers. It was later found out that in general, Blue Star Senior High School’s students are more likely to be extrinsically motivated when they read and the biggest encouragement to their extrinsic motivation is their social circle. While for our main participants, their past experiences were the ones that played important roles in constructing their motivation, either intrinsically or extrinsically.